ChemInform Abstract: Ionothermal Synthesis of Four New Nickel Thiophosphate Anions: [Ni(P2S8)2]2‐, [Ni(P3S9)(P2S8)]3‐, [Ni(P3S9)2]4‐, and [(NiP3S8)4(PS4)]7‐. Issue 12 (14th March 2013) - Cody, Jason A.; Finch, Kenneth B.; Reynders, Gilbert J. III; Alexander, Grant C. B.; Lim, Hyung G.; Naether, Christian; Bensch, Wolfgang
Abstract Compounds (IV)—(VII) are ionothermally prepared from the elements and their structures are determined by single crystal XRD.